Dinamika Problem-Focused Coping Menuju Resiliensi Akademik: Studi Fenomenologis Pada Mahasiswa Tingkat Akhir - Siti Paijatun Solehah; Cut Mellyza Rizka (Universitas Darul Ulum, 2026)
This study aims to explore in depth the dynamics of Problem-Focused Coping (PFC) in building academic resilience among final-year Psychology students currently composing their undergraduate theses. Final-year students often encounter intense academic pressures manifested in anxiety, research stagnation, and interpersonal conflicts with supervisors. Employing a qualitative approach with an interpretative phenomenological design, this research uncovers the essence of participants' conscious experiences in managing these pressures. Data were collected through in-depth interviews with three informants selected via purposive sampling and analyzed using Interpretative Phenomenological Analysis (IPA). The results indicate that PFC dynamics represent a transformative process extending beyond technical task completion, creating a mechanism termed